Hot money and stock market in China: empirical evidence from ARDL and NARDL approaches - Tan, Nian Meng; Fan, Sui Hang; Khor, Ting En; Teng, Xue Wen (2019)
This study discusses the relationship between the stock market performance and all its independent variables which is oil price, economic growth, inflation and hot money in China. The data being used in this study is quarterly data from the period of 2000 to 2017. The main tests being used are Autoregressive Distributed Lag and Non-Autoregressive Distributed Lag which is followed by several diagnostic checking. The test is used to determine whether there exists a long run relationship between the independent variable and stock market performance and if asymmetric effect exist in hot money. The study shows that oil price, economic growth and hot money possess a long run relationship towards stock market performance in China whereas inflation does not. It also shows oil price and economic growth possess a positive relationship whereas hot money and inflation possess a negative relationship. Moreover, it is also found that hot money possesses an asymmetric effect towards stock market performance.